Penerapan Metode Yanbu’a Dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Pada Mata Pelajaran Al-Qur’an Hadist Di Pondok Pesantren Hubbul Qur’an - Muhammad Badran (JURNAL KAJIAN ISLAM MODERN, 2023)
The results of this study aimed to investigate the application of the Yanbu'a Method in improving Al-Qur'an literacy in the Al-Qur'an Hadith subject at the Hubbul Qur'an Islamic Boarding School as many as 15 male students with Minimum Completeness Criteria (KKM) of 75. The Yanbu'a method is a learning approach that focuses on teaching and memorizing the Qur'an using structured repetition and repetition techniques. Through a qualitative approach with case studies at the Islamic boarding school, data were collected through class observations, interviews with teachers, and Al-Qur'an literacy tests. The results showed that the application of the Yanbu'a Method significantly increased the ability of the students with the data that the students had not yet reached KKM in the pre-cycle and 60% achieved KKM in the first cycle and finally the second cycle reached more than 85% in achieving KKM 75 in Al -Qur'an Hadith, with visible improvements in the pronunciation, comprehension, and literacy of the Qur'an. This research provides insight into the effectiveness of this method in improving Al-Qur'an skills in Islamic education institutions, and contributes to the development of appropriate learning methods to achieve the specified KKM.